2008
DOI: 10.1007/s00384-007-0431-7
|View full text |Cite
|
Sign up to set email alerts
|

Hand-assisted laparoscopic total colectomy for slow transit constipation

Abstract: Hand-assisted laparoscopic total colectomy could be a safe and efficient technique in the treatment of STC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 20 publications
3
33
0
6
Order By: Relevance
“…Our data shows that this operation is feasible and safe with no mortality and acceptable morbidity, as reported in previous studies [3][4][5][6][7][8][9][10][11] (Table 5). The early postoperative results highlight problems with bowel function after total colectomy with a mean of 4.4 d until the first bowel movement.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Our data shows that this operation is feasible and safe with no mortality and acceptable morbidity, as reported in previous studies [3][4][5][6][7][8][9][10][11] (Table 5). The early postoperative results highlight problems with bowel function after total colectomy with a mean of 4.4 d until the first bowel movement.…”
Section: Discussionsupporting
confidence: 69%
“…For selected patients presenting with mild disease in the rectum, no dysplasia and with normal rectal compliance, a subtotal colectomy with ileo-distal sigmoid anastomosis may be an alternative and was performed in this study. Few published reports exist and mainly report techniques performed for a single indication or include small numbers of patients [3][4][5][6][7][8][9][10] . The aim of this study was to report the outcomes of laparoscopic total colectomy based on indication, comparing IBD with other indications.…”
Section: Introductionmentioning
confidence: 99%
“…The most common clinical features include refractory constipation, abdominal pain, abdominal distension, and nausea. Necessary physiological examinations include colonic transit test, colonoscopy, anal manometry, defecography, and balloon expulsion [7,8]. In this study, all eligible patients showed positive results in colonic transit test, but the colonoscopy, defecography, manometry, and balloon expulsion showed to be normal.…”
Section: Discussionmentioning
confidence: 76%
“…Pathologically, this disease may be caused by enteric neuropathy resulting from abnormality of the enteric nervous system. Several studies revealed that this abnormality was considered to be related to a decrease in the interstitial cell of Cajal, which was recognized as an intestinal pacemaker and mainly situated in the submucosal and myenteric plexus of the bowel wall [2,7,9]. On the contrary, Toman et al [10] demonstrated that the decreased numbers of interstitial cells of Cajal did not significantly contribute to colonic inertia.…”
Section: Discussionmentioning
confidence: 99%
“…Die generellen Vorteile der laparoskopischen Kolonchirurgie kommen auch hier zum Tragen; insbesondere die niedrigeren Raten an postoperativen Verwachsungen sowie die schnellere Rekonvaleszenz der Patienten stehen hierbei im Vordergrund [33][34][35].…”
Section: Laparoskopische Kolektomieunclassified